2018
DOI: 10.5114/hpc.2018.76518
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of insomnia and depression in patients with age-related macular degeneration

Abstract: Authors' contribution Wkład autorów: A. Study design/planning zaplanowanie badań B. Data collection/entry zebranie danych C. Data analysis/statistics dane -analiza i statystyki D. Data interpretation interpretacja danych E. Preparation of manuscript przygotowanie artykułu F. literature analysis/search wyszukiwanie i analiza literatury G. Funds collection zebranie funduszy SummaryBackground. Age related Macular Degeneration (AMD) affecting the organ of vision, impairs central vision. The study objective was (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Analogous to the existing pool of research on solo-living, there is also a preponderance of varied findings on the inverse relationship linking kin support with insomnia symptoms in the recent literature (e.g., [47][48][49][50][51]). For instance, a study on a group of Taiwanese youth found that having an inadequate amount of support from one's kin was directly related to heightened insomnia complaints ("β = −0.06") (p. 1) [47], while another study on a group of American teenagers has demonstrated that such an experience could also be indirectly predictive of greater insomnia complaints (in this case, at the conclusion of their initial high school year by means of its effect on such sleep difficulties at the start of it) (B = "−.01") (p. 1033) [48].…”
Section: Reduced Support From One's Kinmentioning
confidence: 99%
“…Analogous to the existing pool of research on solo-living, there is also a preponderance of varied findings on the inverse relationship linking kin support with insomnia symptoms in the recent literature (e.g., [47][48][49][50][51]). For instance, a study on a group of Taiwanese youth found that having an inadequate amount of support from one's kin was directly related to heightened insomnia complaints ("β = −0.06") (p. 1) [47], while another study on a group of American teenagers has demonstrated that such an experience could also be indirectly predictive of greater insomnia complaints (in this case, at the conclusion of their initial high school year by means of its effect on such sleep difficulties at the start of it) (B = "−.01") (p. 1033) [48].…”
Section: Reduced Support From One's Kinmentioning
confidence: 99%